From Ritual to Stage: The Social Function of Performance in Traditional and Modern Contexts - Wijaya, Wijaya; Li, Catherine; Ali, Hassan (Yayasan Adra Karima Hubbi, 2026)
Background. Performance has long been an essential part of human society, from its roots in ritualistic practices to its evolution into modern theatrical and performance art forms. Throughout history, performance has served as a means to communicate, express cultural identity, and negotiate social and power dynamics. While traditional rituals held specific social and spiritual functions, contemporary performances often focus on entertainment, self-expression, and cultural critique. Understanding the social function of performance in both traditional and modern contexts is crucial to understanding how societies use performance to address collective values, identity, and power. Purpose. This study aims to explore the social functions of performance in traditional rituals and contemporary theatre, focusing on how these practices facilitate cultural expression, identity formation, and the negotiation of social roles. The research investigates the transformation of performance across historical contexts and its continued significance in modern societies. Method. This qualitative study employs a comparative analysis of selected traditional rituals and modern theatrical performances. Data collection includes field observations, textual analysis of performance scripts, and interviews with practitioners in both domains. Results. The research finds that both traditional rituals and contemporary theatre continue to play key roles in reinforcing and challenging social norms, identity, and power structures. However, the function of performance has evolved, with traditional rituals focusing on spiritual and social cohesion, while modern theatre emphasizes personal expression and critique. Conclusion. The study concludes that performance, whether ritualistic or artistic, remains a critical medium for cultural negotiation, serving both to preserve traditions and to engage with contemporary issues of identity, community, and power.